An evaluation of microwave and RF technology as energy and time efficient alternatives for the drying process of barley malt - Zerva, Evgenia (2016)
The objective of this project was to explore the fundamental interactions between microwave and radio frequency (RF) energy and malt. The main goal was to develop and apply a method for the reduction of time and energy costs and the enhancement of product quality in the kilning process which is used to dry malted barley. Volumetric heating technologies such as microwaves and radio frequency heating have been applied in industrial processing for many years and have the potential to reduce both time and energy costs compared with conventional heating. Potential benefits include savings in energy and process time whilst increasing product homogeneity and thus quality. Furthermore, it was important that the treatment should not adversely affect any of the key brewing (or distilling) quality parameters which are currently specified by the malt end-users. Firstly, the impact of moisture content on the dielectric properties of whole malt and barley grains (variety Tipple) at varying moisture contents relevant to the malting process (5-46% w/w) was investigated. Measurements were obtained using the transmission line waveguide technique, at room temperature (20°C) using microwave frequencies between 2.3 - 2.5 GHz. According to the results, water content was the dominant factor affecting the dielectric properties of both malt and barley grains and there was a strong similarity between malt and barley dielectric properties at a set moisture content, despite their different chemical compositions. The dielectric constant (ε´) of malt increased from 2.14 to 6.54 over the range of 5 to 46% w/w moisture, whereas for barley the equivalent range in ε´ was 2.21 to 6.72. The dielectric loss factor (ε˝) increased with moisture content for both malt and barley from 0.03 to 1.12 and from 0.03 to 1.03 respectively. The outcomes of this work could be applied to the development of microwave processing of malt and barley whole grains. Following the characterisation of these dielectric properties at microwave frequencies, it was decided that the penetration depth of microwaves in barley grains was unlikely to deliver sufficient throughput for an industrial process to be developed. Hence we opted next to investigate the application of radio frequencies (RF) to the drying of malt. We investigated the influence of radio frequency energy applied to malt hydrated to different moisture contents in comparison with a conventional drying process. At the end of the RF processing the moisture content was measured and the amylase activity of the bulk sample was tested. The high and medium loss samples did not maintain the required enzyme activity at the end of the drying process due to high sample temperature effects. In contrast, the low loss samples had better enzyme preservation, despite the fact that high temperatures (>90°C) still existed. This trend 4 could be explained by the fact that the time of the RF treatment in this experiment was less than that in the case of high and medium loss samples. Additional tests were performed to optimise the variable parameters of the RF tunnel system in order to achieve a smoother drying procedure for the malt. The observations from the RF tunnel experiments showed that more extensive study was required to control the temperature effect that was responsible for the deactivation of the amylases. Moreover an additional study on the effect of lower RF frequencies on the drying process of malt in combination with conventional drying could be more promising for the final product quality and for the decrease of time and energy costs.